A fluorescent probe with a vanillin–pyridine–imidazole core structure for carboxylesterase detection in macrophage polarization during bone homeostasis - Xia, Hailong; Wang, Xianghe; Huang, Weichun; Jiang, Xindong; Han, Xionggao; Wang, Chaoyue (Frontiers in Chemistry, 2025)
In this work, a fluorescent probe, VanPI-CarE, with a vanillin–pyridine–imidazole core structure was developed for carboxylesterase (CarE) detection in macrophage polarization during bone homeostasis. The probe responded to CarE with a distinct fluorescence reporting signal at 490 nm upon excitation at 355 nm. Tests in solution showed the advantages of VanPI-CarE, including high sensitivity, excellent stability under various working conditions, high selectivity, and low cytotoxicity. Further confocal imaging indicated that VanPI-CarE enabled visualization of CarE level in living macrophages. The probe further revealed macrophage polarization in bone homeostasis under both induction and inhibition conditions via CarE detection. These findings provide meaningful insights for inflammation-related research.